2006
DOI: 10.1590/s0004-27492006000600005
|View full text |Cite
|
Sign up to set email alerts
|

Anterior ischemic optic neuropathy: a comparison of the optic disc area of patients with the arteritic and non-arteritic forms of the disease and that of normal controls

Abstract: NA-AION occurs predominantly in small discs while the arteritic form of the disease shows no such preference. Factors related to optic disc structure play a role in the pathophysiology of NA-AION. The occurrence of AION in large optic optic discs should raise the suspicion of temporal arteritis. On the other hand, small optic disc areas do not rule out that vasculitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
(32 reference statements)
0
18
0
3
Order By: Relevance
“…The fellow eye is involved in up to 15% of patients within 5 years, but the risk of recurrence in the same eye is less than 5%. There is no treatment for acute NAION but it is essential to evaluate these patients for underlying treatable atheromatous vascular risk factors and to prevent precipitating factors such as blood loss, sleep apnea syndrome or nocturnal hypotension (6)(7)(8) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fellow eye is involved in up to 15% of patients within 5 years, but the risk of recurrence in the same eye is less than 5%. There is no treatment for acute NAION but it is essential to evaluate these patients for underlying treatable atheromatous vascular risk factors and to prevent precipitating factors such as blood loss, sleep apnea syndrome or nocturnal hypotension (6)(7)(8) .…”
Section: Discussionmentioning
confidence: 99%
“…Most of these clinical characteristics are similar to those found in cases with typical NAION, not related to glaucoma although in the latter the disc edema tends to be segmental and the altitudinal field defect generally occurs inferiorly. The presence of optic disc with small or absent physiologic cup is a frequent finding in both in typical NAION and in cases secondary to acute glaucoma (6)(7) . Therefore, although we can find some differences and similarities in clinical findings of patients with NAION after acute rise of IOP and patients with typical idiopathic NAION, the number of cases of NAION after acute glaucoma is so small that one a clear distinction between the two modalities of ischemic optic neuropathies cannot be established.…”
Section: Discussionmentioning
confidence: 99%
“…Also, various studies have reported that topographic features of the ONH has a characteristic role in the progression of some ocular diseases such as NAION and Leber's Hereditary Optic Neuropathy (LHON) [10][11][12][13] . A small optic disc characterizes eyes with optic nerve axon crowding and it is well known that a small and crowded disc is a risk factor for NAION.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has some advantages such as obtaining rapid imaging without pupil dilatation, imaging in blurred media and high repeatability. The HRT analysis simply yields more information and more parameters [8][9][10][11][12][13] . In this study, topographic features of the ONH in diabetic eyes were investigated with HRT III.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation